2017
DOI: 10.1007/s11356-017-9714-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of chemical constituents from Piper against the environmental burden Aedes aegypti Liston and their impact on non-target toxicity evaluation against biomonitoring aquatic insects

Abstract: Dengue is the most rapidly spreading mosquito-borne viral disease in the world. The mosquito, Aedes aegypti, also spreads Yellow fever, Chikungunya, and Zika virus. As the primary vector for dengue, Ae. aegypti now occurs in over 20 countries and is a serious concern with reports of increasing insecticide resistance. Developing new treatments to manage mosquitoes are needed. Formulation of crude volatile oil from Piper betle leaves (Pb-CVO) was evaluated as a potential treatment which showed larvicidal, ovipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The plants tested in the present study are reported to be eco-friendly and toxic to agriculturally important insect pest [ 20 ]. For example, essential oils from Citronella and Eucalyptus are often used in repellents sold under several brand names [ 21 ]. Recent studies have indicated that phytol, a precursor of synthetic vitamin E and vitamin K (which was identified in our analysis as well), exhibits antioxidant and antinociceptive effects and was cytotoxic against the MCF−7 breast cancer cell line [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plants tested in the present study are reported to be eco-friendly and toxic to agriculturally important insect pest [ 20 ]. For example, essential oils from Citronella and Eucalyptus are often used in repellents sold under several brand names [ 21 ]. Recent studies have indicated that phytol, a precursor of synthetic vitamin E and vitamin K (which was identified in our analysis as well), exhibits antioxidant and antinociceptive effects and was cytotoxic against the MCF−7 breast cancer cell line [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…aegypti at the minimal dosage of 10 ppm (Lija-Escaline et al, 2015). Similarly, Vasantha-Srinivasan et al (2018) reported that P. betle CVO derived from P. betle at the sub-lethal dosage damage the pM, and major alteration in the alignment of EL and GL of dengue mosquito comparable to the control. Previous research on Andrographolide a major derivative of A. paniculata against dengue mosquito gut cells proved that there was an unembellished collapse in the mid-gut pM, in addition to a chief variation in the El and GL alignment (Edwin et al, 2016).…”
Section: Impact Of Phytochemicals On Midgut Tissuesmentioning
confidence: 86%
“…Plant volatile oils were also conveyed with mosquitocidal potentials. As studied by Vasantha-Srinivasan et al (2018), the crude volatile oil (CVO) from Piper beetle leaves possessed significant larvicidal, ovipositional, and repellency effects against Ae. Aegypti.…”
Section: Biological Management Of Mosquitoesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Vasantha-Srinivasan et al. reported the level of α- and β-carboxylesterase was significantly altered by the activity of metabolites [ 92 ].…”
Section: Discussionmentioning
confidence: 99%